(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
The effect of the lanthanide shift reagent (LSR) – tris(6,6,7,7,8,8,8-heptafluoro-2,2-dimethyl-3,5-octa-dionate) of Europium – Eu(fod)3 – on 1H NMR spectra of functionalized 3-arylisocoumarins and 3-aryl-3,4-dihydroisocoumarins was investigated. Based on previous studies of LSR interactions with benzopyrones, it was expected that the main coordination centre for the Eu3+ would be the exocyclic Oxygen atom of the heterocycle, but the possibility of competition from aromatic substituent functional groups was also considered. By measuring lanthanide-induced shifts (LIS) of the proton signals of the molecules at different ratios of substrate and Eu(fod)3, specific LIS values were determined. Based on those, it was concluded that the main direction of LSR coordination with 3-(2-hydroxy-5-methylphenyl)-1H-isochromen-1-one, 3-(2-methoxy-5-methylphenyl) 1H-isochromen-1-one and 3-(2-methoxy-5-methylphenyl)isochroman-1-one is the exocyclic Oxygen atom of the heterocycle, because the maximum LIS were recorded for the H-8 atom of isochromone system of these derivatives. In the case of ethyl ester of [2-(4-(1-oxo-1H-isochromen-3-yl)phenoxy] acetic acid and methyl ester of [2-(4-(1-oxoisochroman-3-yl)phenoxy]acetic acid comparable LIS values were observed both for H-8 and for the methylene group of the hydroxyacetic acid fragment, therefore, in such molecules the coordination of the Eu3+ to the heterocycle or to the aliphatic ester group is almost equally probable. In spectrum of methyl ester of N-[4-(1-oxo-1H-isochromen-3-yl)phenoxy]acetylvaline and N-[4-(1-oxoisochroman-3-yl)-phenoxy]acetylvaline there are insignificant LIS of H-8; and the maximum LIS were observed for the signals of the protons neighboring the two carbonyl groups of hydroxyacetic acid and valine fragments. Thus, these compounds interact with LZR simultaneously by a neighboring amide and aliphatic ester group, which allows us to conclude that a chelate-type complex is formed.